Eine Methode der Subtraktion des extrarenalen Backgrounds in der dynamischen 131J-Hippuran Szintigraphie - Ewa, Mlodkowska; Liniecki, J.; Surma, M. (Nuklearmedizin - NuclearMedicine, 1979)
Using a Toshiba GC-401 gamma camera with MDS computer Trinary a new method was developed for subtracting the extrarenal (extracanalicular) “background” from the count rate recorded over the kidneys after intravenous administration of 131I-hippurate. Mean subtraction factors of the “blood” activity curve were calculated from a study of 27 patients who were given 51Cr-HSA for purposes of conventional renography with “background” subtraction.The values of the mean subtraction factors FR>L for the right and left kidney, by which a blood count rate should be multiplied amounted to 0.86 ± 0.12 and 0.79 ± 0.13, respectively.A comparison of the coefficients of variation of the pure renal signal when mean vs. individually determined subtraction factors were used, and the verification of the method in unilaterally nephrectomized patients have demonstrated that determination of the factors, FR?L, for each patient individually is not required and sufficient precision can be obtained by using the method and factors reported in this study.